Fossil-calibrated molecular phylogenies reveal that leaf-mining moths radiated millions of years after their host plants. - Lopez-Vaamonde, C; Wikström, N; Labandeira, C; Godfray, H; Goodman, S; Cook, J (2006)
Coevolution has been hypothesized as the main driving force for the remarkable diversity of insect-plant associations. Dating of insect and plant phylogenies allows us to test coevolutionary hypotheses and distinguish between the contemporaneous radiation of interacting lineages vs. insect 'host tracking' of previously diversified plants. Here, we used nuclear DNA to reconstruct a molecular phylogeny for 100 species of Phyllonorycter leaf-mining moths and 36 outgroup taxa. Ages for nodes in the moth phylogeny were estimated using a combination of a penalized likelihood method and a Bayesian approach, which takes into account phylogenetic uncertainty. To convert the relative ages of the moths into dates, we used an absolute calibration point from the fossil record. The age estimates of (a selection of) moth clades were then compared with fossil-based age estimates of their host plants. Our results show that the principal radiation of Phyllonorycter leaf-mining moths occurred well after the main radiation of their host plants and may represent the dominant associational mode in the fossil record.